Pengaruh Beban Kerja, Dukungan Sosial dan Pengalaman Kerja terhadap Kepuasan Kerja Pegawai di PT. Kereta Api Indonesia Binjai - Santika Br Situmorang; Saimara A.M Sebayang (Pusat Riset dan Inovasi Nasional, 2025)
This study was conducted at PT. Kereta Api Indonesia Binjai to analyze the effects of workload, social support, and work experience on employee job satisfaction. Job satisfaction is a vital aspect of human resource management since satisfied employees tend to perform optimally, remain loyal, and contribute positively to organizational goals. The research involved 78 employees who served as both the population and the sample, selected through a saturated sampling method. Primary data were obtained through questionnaires and observation, while secondary data were sourced from literature studies. Data analysis applied validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing using t-tests and F-tests. The findings indicate that workload, social support, and work experience positively and significantly affect job satisfaction, both partially and simultaneously. The coefficient of determination (R²) of 0.894 shows that the three independent variables explain 89.4% of job satisfaction, while the remaining 10.6% is influenced by factors beyond this study, such as compensation, training, and career development. Among the variables, workload has the strongest influence with a coefficient of 0.942, followed by work experience at 0.771, and social support at 0.198. This highlights that a balanced workload aligned with employee capacity, adequate social support from supervisors and peers, and practical experience gained through training and practice are key determinants of job satisfaction. The study recommends that the company focus on fair workload distribution, stronger workplace interaction, and continuous training to improve employee experience. Leadership should also encourage skill development through case studies and structured programs, enabling employees to face challenges more effectively and contribute to the company’s sustainable performance and growth.